2017
DOI: 10.1002/star.201700014
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characteristics of mechanical and functional properties of starch/Plantago psyllium seeds mucilage films

Abstract: The aim of the present study was to reinforce starch‐based films with psyllium mucilage in order to obtain natural, edible, and biodegradable films with improved mechanical and functional properties. The rheological properties of film‐forming solutions can be controlled by the concentration levels of added mucilage. The addition of mucilage reduced the decomposition of the system, which made these films more thermally stable. Those starch–mucilage films were sufficiently transparent and exhibited a low aqueous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 30 publications
(49 reference statements)
1
26
1
1
Order By: Relevance
“…In the case of psyllium, despite only a few previous studies, the same behaviour could be expected. Interestingly, different from our study, Krystyjan et al (2017) observed an increase in G′ and G′′ when psyllium was added to starch to obtain gels, but, as in the studies with xanthan gum, the concentration of solids used in the samples was much lower than in our study. xanthan gum.…”
Section: Rheologycontrasting
confidence: 97%
See 1 more Smart Citation
“…In the case of psyllium, despite only a few previous studies, the same behaviour could be expected. Interestingly, different from our study, Krystyjan et al (2017) observed an increase in G′ and G′′ when psyllium was added to starch to obtain gels, but, as in the studies with xanthan gum, the concentration of solids used in the samples was much lower than in our study. xanthan gum.…”
Section: Rheologycontrasting
confidence: 97%
“…También es posible utilizar el psyllium para obtener películas biodegradables Krystyjan et al, 2017;Sukhija et al, 2016) con mayor resistencia a la tracción, más termoestables y menos permeables y solubles al vapor de agua.…”
Section: • Postres Lácteosunclassified
“…Plantago psyllium seeds have been used for a long time, mainly in pharmaceutical industry (Craeyveld et al 2009, Singh 2007 and to a smaller extent also in the food processing plants. There are known attempts to use it as additives in burgers and beef sausage production (Osheba et al 2013) and for obtaining starch-based edible films (Krystyjan et al 2017). This raw material was used in cookie production as the form of psyllium fibre (Raymundo et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As was confirmed by statistical analysis, there were no differences in thickness between the composites. The tensile strength of Hyal composite was at a high level and was many times higher than composites made from other natural biodegradable polymers such as: starch [ 43 , 44 ], chitosan [ 45 ], cellulose acetate (CA) and cellulose nanofibers (CNF) [ 46 ].…”
Section: Resultsmentioning
confidence: 99%